Acoustic calculation of combustion process in internal combustion engine based on wave equation. (28th November 2011) - Wei, Haiqiao; Shu, Gequn; Wei, Jingsi
The combination of the acoustic theory and the combustion model can calculate the pressure wave in the cylinder. The wave equation of pressure oscillation during combustion in the diesel engine was derived and investigated by using the acoustic model and KIVA combustion simulation programme. The oscillation characteristics at different positions in the combustion chamber were analysed through comparison of the calculated results and the experimental results; the two results were in good agreement. The effects of cylinder bore, octane number, and compression ratio and intake air temperature on the in-cylinder pressure fluctuations were analysed. The results showed that the combination of the pressure wave equation and the KIVA combustion programme is a good method to calculate the pressure fluctuation in the cylinder. It is expected that the method can be used to predict noises produced by combustion and to deepen understanding about the nature of internal combustion engine noise.